Antioxidant activity of citrus fruits cultivated in Brazil - Duzzioni, A. G.; Franco, A. G. [UNESP]; Lenton, V. M.; Sylos, C. M. [UNESP]; Narain, N. (Int Soc Horticultural Science, 2018)
Citrus fruits are known for their phytochemical constituents with antioxidant activity. Seven cultivars of citrus fruits were evaluated for ascorbic acid, total phenolics, total flavonoids and total carotenoids (expressed as beta-carotene mu g mL(-1)) as well as determining the presence of flavanones. We also assessed the reduction potential via free radical, DPPH center dot, of fruit juice and extracts of carotenoids and flavanones after isolation. Lemon contained the highest content of ascorbic acid (237.0 +/- 14.72 mg AA 100 mL(-1)) and the lowest content of total phenolics (453.8 +/- 28.27 mg gallic acid 10 mL(-1)). Ponkan tangerine obtained significantly the highest content of total carotenoids (7.665 +/- 1.290 mg beta-carotene mL(-1)) and of total flavonoids (128.5 +/- 16.95 mg rutin mL(-1)). The EC50 was greater for 'Murcott' tangor. Of the five different types of flavanones evaluated in this study (eriocitrin, naringin, hesperidin, neohesperidin and poncirin), only hesperidin was present in all the fruits.
Keywords: flavanones; carotenoids; HPLC and DPPH center dot